2023
DOI: 10.3390/biomedicines11061535
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Activity of Trace Element Germanium Including Anticancer Properties

Abstract: Germanium is an essential microelement, and its deficiency can result in numerous diseases, particularly oncogenic conditions. Consequently, water-soluble germanium compounds, including inorganic and coordination compounds, have attracted significant attention due to their biological activity. The review analyzes the primary research from the last decade related to the anticancer activity of germanium compounds. Furthermore, the review clarifies their actual toxicity, identifies errors and misconceptions that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 166 publications
0
4
0
1
Order By: Relevance
“…Germatrane derivatives have shown strong antitumor and antioxidant activity. The bicyclic analogues of germatranes-germocanes and monocyclic analoguesand hypogermatranes have been found to possess the same activity [120].…”
Section: Germaniummentioning
confidence: 95%
“…Germatrane derivatives have shown strong antitumor and antioxidant activity. The bicyclic analogues of germatranes-germocanes and monocyclic analoguesand hypogermatranes have been found to possess the same activity [120].…”
Section: Germaniummentioning
confidence: 95%
“…It is the lack of this important element in the body that can cause the development of oncological processes. [18] Drinking goji juice has a positive effect on health -it shows good results in the treatment of cancer of the liver, prostate, colon, breast and other organs. [19]…”
Section: Effective In the Treatment Of Cancermentioning
confidence: 99%
“…However, the mechanism of this antioxidant effect remains unclear. Recent studies have proposed the hypothesis that germanium derivatives catalyze the decomposition of hydrogen peroxide [40]. Trace germanium can keep hydrogen peroxide at a low level, thus inhibiting/preventing oxidative stress.…”
Section: The Anti-oxidation Effectmentioning
confidence: 99%
“…Trace germanium can keep hydrogen peroxide at a low level, thus inhibiting/preventing oxidative stress. It has been observed that germanium is part of the active centers of some enzymes and participates in oxidation, mainly with hydrogen peroxide, without producing harmful reactive oxygen species [40]. In fact, previous results suggest that Ge-132 has the potential to act as an antioxidant supplement by protecting cells from oxidative damage [41].…”
Section: The Anti-oxidation Effectmentioning
confidence: 99%